Virtual Religion and Digital Engagement: Constructing Muslim Self-Identity - Kinkin Yuliaty Subarsa Putri; Adamu Abbas Adamu; Zhao Wanbin; Benni Setiawan; Mega Ayu Permatasari; Noprita Herari; Luthfi Fazli (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
The primary objective of this study is to examine how digital media literacy influences online religious engagement and identity formation among Indonesian Muslims, considering the role of personal comprehension of Islamic teachings. A quantitative survey was conducted with 320 adult participants from diverse regions who actively followed Islamic preachers on social media platforms. The methodology tested sequential relationships among digital media literacy, virtual religion engagement, self-identity, and cultural identity. Results indicate that higher levels of digital media literacy are associated with more reflective engagement with online religious content, which strengthens self-identity and reinforces cultural identity. Findings also reveal that individual depth of religious understanding provides a critical foundation for responsible interpretation of digital content, while media literacy enhances the ability to critically evaluate information, navigate platform dynamics, and engage ethically. Overall, the study demonstrates that combining strong personal religious knowledge with digital media literacy supports informed, reflective, and culturally grounded religious participation. These outcomes highlight the strategic role of digital literacy in shaping contemporary religious experiences and sustaining both personal and communal dimensions of faith in digital environments.